2014
DOI: 10.1002/2013jd021141
|View full text |Cite
|
Sign up to set email alerts
|

The spatial scale dependence of water vapor variability inferred from observations from a very tall tower

Abstract: Recent studies have established that atmospheric water vapor fields exhibit spatial spectra that take the form of power laws and hence can be compactly characterized by scaling exponents. The power law scaling exponents have been shown to exhibit substantial vertical variability. In this work, Taylor's frozen turbulence hypothesis is used to infer the first‐order spatial structure function and generalized detrended fluctuation function scaling exponents for scales between 1 km and 100 km. Both methods are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Wood and Field (2011) observed that the cloud-chord-length distributions derived from the MODIS imager are essentially indistinguishable between the across-track and along-track directions, implying that the cloud-chord-length distributions are horizontally isotropic. Pressel and Collins (2012) found that temperature and specific humidity soundings from the Atmospheric Infrared Sounder (AIRS) instrument largely exhibit horizontal isotropy. Therefore, the twodimensional curtain sampling of CloudSat can be viewed as representative of the three-dimensional atmosphere.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Wood and Field (2011) observed that the cloud-chord-length distributions derived from the MODIS imager are essentially indistinguishable between the across-track and along-track directions, implying that the cloud-chord-length distributions are horizontally isotropic. Pressel and Collins (2012) found that temperature and specific humidity soundings from the Atmospheric Infrared Sounder (AIRS) instrument largely exhibit horizontal isotropy. Therefore, the twodimensional curtain sampling of CloudSat can be viewed as representative of the three-dimensional atmosphere.…”
Section: Datamentioning
confidence: 99%
“…The scale dependence of atmospheric fields and their variability are routinely explored using observations, numerical simulations, and theoretical models (e.g., Lovejoy 1982;Nastrom and Gage 1985;Nastrom et al 1986;Cahalan et al 1994;Tjemkes and Visser 1994;Pierrehumbert 1996;Cho et al 1999;Wood and Taylor 2001;Lindborg 2007;Kahn and Teixeira 2009;Bacmeister and Stephens 2011;Kahn et al 2011;Pressel and Collins 2012;Fischer et al 2013;Pressel et al 2014;Barker et al 2017). Wood and Field (2011) show that the probability distribution function (PDF) of horizontal cloud sizes from the Moderate Resolution Imaging Spectroradiometer (MODIS) follows a power law characterized by an exponent of approximately 25/3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using aircraft-based lidar observations, Fischer et al (2013) showed that values of 𝛽 for height-resolved q are near −5/3 in air masses with deep convection, while values of 𝛽 are in excess of −2 in nonconvective air masses. Over land using surface-based tower observations, Pressel et al (2014) showed that q have values of 𝛽 near −5/3 in the convective mixed boundary layer and values of 𝛽 in excess of −2 in the nocturnal boundary layer. Similar results were obtained over the SEP Ocean using VOCALS-REx in situ aircraft observations (K11).…”
Section: Relationship Between Column Water Vapor and 𝛼 Smentioning
confidence: 99%
“…Power law exponents for a variety of quantities can vary strongly with altitude, latitude, cloud regime, and diurnal and seasonal cycles (e.g., KT09; Nastrom & Gage, 1985; Pressel et al., 2014) and can be anisotropic between the horizontal and vertical directions (Lovejoy et al., 2010). The spectral breaks that are observed around 400–800 km typically emerge from climatological averages.…”
Section: Introductionmentioning
confidence: 99%